Analisis Kelengkapan Pengisian Ringkasan Pasien Pulang (RM 05) Guna Menunjang Mutu Rekam Medis Di RS X - Rafied Ridwan Firmansyah; Meira Hidayati (Jurnal Health Sains, 2021)
Medical record is a record that describe all important information regarding the patient, therefore the completeness of the medical record in hospital is very important, especially on the discharge summary. The aim of the research was to find out the process of analyzing the completeness of discharge summary to support the quality of medical records at X Hospital. The research type is a qualitative descriptive, data collection were carried out by observation and interviews. The results of completeness aspect, the complete items are knowing the patient's identity, diagnosis, disease history, physical and supporting examinations, treatment during hospitalization, allergy choice, drug side effects and information required for control. The incomplete item is the condition of the patient when leaving the hospital (90.1%). In the aspect of accuracy, 96.7% of the form is clearly legible, while error correction is the lowest item at 74.7%. In the aspect of punctuality, 75.8% were on time, while 24.2% were not. In the legal aspect, only one indicator that has not fulfill the legal aspect, namely doctor’s authentication. The conclusion of this research is the implementation of discharge summary form at Hospital X, is in accordance with the SOP. However, the implementation is still not optimal